Parasites, pathogens, and pests of honeybees in Asia - Chantawannakul P. (2017)
© 2015, INRA, DIB and Springer-Verlag France. Asia is home to at least nine honeybee species, including the introduced Apis mellifera. In addition to A. mellifera and Apis cerana being widely employed for commercial beekeeping, the remaining nonmanaged species also have important ecological and economic roles on the continent. Species distributions of most honeybee species overlap in Southeast Asia. This promotes the potential for interspecific transmission of pests and parasites and their spread to other parts of the world by human translocation. The decline of honeybee populations is of great concern around the world, including in Asia. The global colony losses of A. mellifera are believed to be caused, in part, by parasites, pathogens, and pests originating from Asia, such as the mite Varroa destructor, the microsporidian Nosema ceranae, and some bee viruses. This review discusses important pests, pathogens, and parasites in both the introduced A. mellifera and native honeybees in Asia to provide an overall picture of honeybee health in the region and future threats to the apiculture industry.